Pengaruh Ketebalan Lapisan TiO2 terhadap Performasi Dye Sensitized Solar Cells: Nurrisma Puspitasari, Nurul Amalia Silviyanti, Gatut Yudoyono, Gontjang Prajitno, Agus Rubiyanto, Endarko - Nurrisma Puspitasari Nurrisma Puspitasari; Nurul Amalia Silviyanti Nurul Amalia Silviyanti; Gatut Yudoyono Gatut Yudoyono; Gontjang Prajitno Gontjang Prajitno; Agus Rubiyanto Agus Rubiyanto; Endarko Endarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Dye Sensitized Solar Cell (DSSC) is the third generation of solar cells. DSSC is formed by sandwich structure, there are five parts: ITO glass (Indium Tin Oxide) as substrate; TiO2 as semiconductor material; dye (chlorophyll-turmeric-mangosteen) as an electron donor; gel electrolyte as electron transfer and active carbon as a catalyst in the counter electrode. The synthesis of nanometer-sized TiO2 powder is obtained by coprecipitation method. From the research that has been done, the efficiency of DSSC with 10 µm TiO2 layer thickness bigger than 20 µm and 30 µm layer thickness. The DSSC efficiency result is 0.25% for 10 µm TiO2 layer thickness , 0.143% for 20 µm TiO2 layer thickness, and 0.195% for 30 µm TiO2 layer thickness.